"Shock and Go?" extracorporeal cardio‐pulmonary resuscitation in the golden‐hour of ROSC. Issue 5 (17th June 2016) - Spangenberg, Tobias; Meincke, Felix; Brooks, Stephanie; Frerker, Christian; Kreidel, Felix; Thielsen, Thomas; Schmidt, Tobias; Kuck, Karl‐Heinz; Ghanem, Alexander
Abstract : Objectives: The feasibility and outcomes of 35 consecutive patients subjected to eCPR in the tertiary cardiology center were investigated. Background: While conventional cardiopulmonary‐resuscitation (cCPR) often times achieves only mediocre outcomes extracorporeal cardiopulmonary‐resuscitation (eCPR) increasingly shifts into the focus of interest. However, the scientific evidence for eCPR is sparse, particularly in the cardiological setting. Methods: Retrospective chart analysis of 35 patients treated with eCPR between 01/2014 and 10/2015. Results: The duration of cCPR until initiation of eCPR was 73.8 ± 37.6 min and resulted in an initial pH of 6.9 ± 0.2 and serum lactate level of 14.5 ± 4.8 mmol/L. About 62% ( n  = 22) of the patients suffered from out of hospital cardiac arrest (OHCA), 85% ( n  = 30) of the overall events were witnessed and bystander‐CPR performed in 77% ( n  = 27) of cases. Cause of arrest was dominated by acute myocardial infarction (AMI, 71%), initial rhythm to a lesser degree by ventricular fibrillation/tachycardia (VF/VT, 57%). Almost all patients ( n  = 33, 94%) experienced return of spontaneous circulation (ROSC) after establishing extracorporeal life support (ECLS). In all 57% patients were successfully weaned from ECLS. Survival to discharge was 31% with predominantly good cerebral performance category (CPC 1‐2). Survivors were more likely to receive bystander‐CPR ( P  = 0.03) and the duration of cCPR until initiation of eCPR was significantly shorter ( P  = 0.004). Conclusions: Our data proves the exceptional level of efficiency of eCPR particularly when Bystander‐CPR has been initiated and there is a short duration of cCPR. © 2016 Wiley Periodicals, Inc.